Regional integration and African economic development: sustainable development or underdevelopment - D.C, Ndidigwe (SPC Journal of Social Sciences, 2020)
The issue of African development through cooperation has been a subject of discourse and a top agenda among scholars and political actors in Africa for more than five decades. The proliferation of regional economic groupings in the early 1970s and the 1980s can attest to the priority given to these schemes by various governments in Africa. However, despite the momentum that regional cooperation as a means to African development gathered, the continent had a little to show for its implementation. This paper examined the dynamics of regional integration programs embarked upon in the continent, especially by critically examining the various regional programs of two leading Africaâ€™s sub-regional organizations and groupings that are somewhat formidable in the continent, to wit: the Economic Community of West African States ( ECOWAS) and the Southern African Development Community ( SADC) whose mandate and objective are development driven and ultimately self reliance. Data for this paper was retrieved mainly from secondary source of scholarly articles and books. Above all the paper submits that there is an association between regional integration and sustainable development in Africa. By this, regional integration remains irreducible minimum desiderata for the continentâ€™s development. The paper therefore recommends that participating countries should muster strong political will to make integration functional and funding of development programs should be sourced largely internally.Â